Penguatan Wawasan Manajerial melalui Pembelajaran Lapangan pada UMKM Kampung Keramik Dinoyo : Studi pada Yan’s Keramik Malang - Bilqis Nabila Istiqlaliani; Auramila Divana Esfiandari; Agung Winarno; Agus Hermawan (Jurnal Pengabdian Masyarakat, 2026)
This community service activity is motivated by the limited managerial capacity, suboptimal digital marketing practices, and operational inefficiencies in craft-based SMEs, particularly Yan’s Keramik located in the Dinoyo Ceramic Village, Malang City. The objective of this activity is to identify business problems comprehensively and strengthen managerial insights through field-based learning. The method employed is a participatory approach combined with experiential learning and action research, consisting of planning, implementation, and reflection stages. Activities include observation, interviews, hands-on ceramic production practice, and assistance in developing digital marketing content planning. The results indicate that direct student involvement provides a comprehensive understanding of the production process, from shaping to firing, and highlights the importance of precision in maintaining product quality. Furthermore, production activities and pottery classes are identified as valuable promotional content that has not been optimally utilized. The assistance provided encourages business owners to manage content more systematically and recognize daily activities as part of their marketing strategy. Although the changes are still at an early stage, this activity establishes a foundation for gradual capacity building, particularly in digital marketing and managerial awareness.